Lesser Redpolls Acanthis cabaret undertake post-breeding and post-juvenile moult during autumn movements. Issue 2 (1st December 2016) - Walton, Clive
ABSTRACT: A previous study suggested that Lesser Redpolls Acanthis cabaret in northern England moult before migration. Redpolls caught on autumn passage at Easter Inch Moss in the central lowlands of Scotland show a pattern of recoveries consistent with a north-to-south movement. Both adult and first-calendar-year Lesser Redpolls of these northern populations were moulting when they passed through Easter Inch Moss during the autumn migration, which continued into October and late November. These results suggest that Lesser Redpolls in northern Britain leave their breeding grounds and start their autumn migration while moult is in progress.